Novel concepts for characterisation of heterogeneous particulate surfaces - Peukert, Wolfgang; Mehler, Carsten; Götzinger, Martin (Applied Surface Science, 2002)
Surface properties of fine particles are of high relevance in several technical applications, such as nanotechnology, adsorption or crystallisation. Particulate surfaces are not well-defined, may contain flaws and dislocations, internal stresses and all kinds of impurities. Thus, these surfaces are structurally and energetically heterogeneous. Their interactions are, therefore, poorly understood. Adsorption equilibria, adhesion forces or contact angles reflect the interaction of molecules and particles with surfaces and fluid phases. Modelling of these elementary processes leads to mean or distributed surface properties of technical surfaces and small particles. The dispersive interactions of heterogeneous surfaces are characterised by mean parameters like a Hamaker constant. Henry coefficients of gases on activated carbon, graphite and alumina have been quantitatively described as a function of the critical temperature and pressure of the respective adsorptive and the Hamaker constant of the solid. Conversely, Hamaker constants determined from adsorption experiments are used to predict measured adhesion forces of alumina particles. Polar interactions are described by a new approach derived from continuum models of liquids. The particle surface is characterised by a density distribution of partial charges on small surface patches. By means of a statistical mechanical approach Henry coefficients both in the gas and liquid phase can be described quantitativel
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.novelc_8
Keywords: Particle surfaces; Characterisation; Adsorption; Adhesion